The Effect of Benzo(A)Pyrene on Male Mouse Mus Musculus - Hanachi, Parichehr (2002)
A study was carried out to determine the effect of benzo(a)pyrene (BaP) on selected enzyme activities, the pathology of lung, liver and kidney and cellular aspects of the mice Mus musculus. A suppression or change in the activities of several enzymes in these tissues can be used as a potential technique for the diagnosis of carcinogenesis in the early stage. The initial work involved the evaluation of lethal dose and the threshold dose required for induction of carcinogenesis in adult mice. Subsequent work involved the determination of glutathione S-transferase (OST) and glutathione peroxidase (OPx) activities over a time period during which the mice were treated with benzo(a)pyrene. Finally, induction of OST and OPx was achieved by long-term treatment with BaP. The OST was purified partially by affinity chromatography. Determination of the effect of BaP on the histology of liver, lung, kidney of mice were also carried out. Results obtained showed that GST and GPx activities were induced by BaP in a dose-dependent manner (100-250 mg/kg body weight). The mice were injected with BaP at a dose of 200 mg/kg body weight once at the start of the short term study, GST activity was induced at maximum after 4 days, and after that the activity dropped to almost normal values. The effect of BaP on GST and GPx activities in the liver, lung, kidney and blood of male mice were studied in long-term study. The mice with injected 200 mglkg BaP once a week for 8 weeks. The GST activity was significantly increased (P<0.05) after 2 weeks in liver, lung, kidney and blood while GPx activity was significantly increased (p<0.05) in liver and lung with hydrogen peroxide as the substrate after 4 and 8 weeks, GPx activity did not change when cumene hydroperoxides was used as a substrate. Histological changes in the liver and lung was observed after 2 weeks and in the kidney after 4 weeks of treatment. The kidney showed mild inflammation after 4 weeks. Liver histology of mice treated after 2 weeks showed some cells with binucleation and after 4 weeks showed degeneration and necrosis and hepatocytes were slightly enlarged. The lung cells showed severe acute inflammation after 2 weeks and after 4 weeks showed sever epitelization and the cells lost their normal shape and arrangement and the nuclei become hyperchromatic after 8 weeks. Attempts to purify GST in the mice were carried out using GSH-sepharose affinity matrix. The cytosolic GST purified in this study resolved into three discrete molecular species of approximate molecular weight 25271 D, 23478 D and 25839 D respectively comparable to the previously designated isoforms MI, MII and MIII. The GST in the BaP treated sample exhibited electrophoretic migration on SDSPAGE closely similar to the normal control. Purified liver GST had higher specific activity than the lung and the subunits were of comparable size. This may indicate the existence of common GST isoform in both organs. The main finding in this research related to result of IEF. It showed three activity peaks in the normal control and B aP treated samples livers with different pIs and substrate specificities. The GST activity toward ethacrynic acid in the treated mice was significantly higher than nonnal control indicating BaP induced the GSTMII (class Pi). In this study, laboratory trials with biochemical measurements supported by toxicity and histological studies were tested as tools for the assessment of the environmental hazard of BaP to target organisms.